1979
DOI: 10.1055/s-0028-1092753
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Activities of Fatty Acid Synthesis Enzymes in Insulin-Resistant Adipocytes from Spontaneously Obese Rats

Abstract: Acetyl coenzyme A carboxylase and fatty acid synthetase activities were studied to determine the biochemical basis of the markedly impaired capacity of fat cells from spontaneously obese, old rats to convert glucose to fatty acids relative to cells from lean, young rats. Michaelis constants for the substrates of both enzymes were similar in large and small adipocyte homogenates. In contrast, Vmax values were over 80% less in homogenates from large relative to small cells on a per cell basis. Long-term dialysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…These findings are in line with previous publications reporting downregulation of lipogenic mRNAs in WAT of obese humans 2729 and rodents 30,31 . In addition to the suppression of DNL enzymes, we observed a profound downregulation of GLUT4 in VAT of obese subjects (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in line with previous publications reporting downregulation of lipogenic mRNAs in WAT of obese humans 2729 and rodents 30,31 . In addition to the suppression of DNL enzymes, we observed a profound downregulation of GLUT4 in VAT of obese subjects (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…FASN is robustly expressed in many solid tumors and early tumorigenic lesions in the colon and supports tumor cell proliferation and survival through enhanced lipogenesis and anti-apoptosis [44], [45]. Given that FASN and mTOR are mediators of insulin action [46], [47] and ME1 has been proposed to augment insulin secretion [48], the decrease in proliferation-associated gene expression with dietary SPI and loss of ME1 is consistent with attenuated insulin action in distal colon and jejunum. The observed reduction in colon mTOR gene expression with dietary SPI also may also be related to levels of leptin, adiponectin and/or other serum factors; alternatively, it may reflect inhibition by as yet unknown bioactive component(s) in SPI [49], [50].…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have addressed the point that adipocyte DNL is a highly regulated pathway, as in fasting [55] and obesity [19], [20], [56], [57], and it is generally correlated with the degree of systemic insulin sensitivity [27], [28], [37], [40], [56], [57]. Our studies further confirm that suppression of the adipose DNL pathway and deterioration of systemic glucose metabolism are tightly correlated very early in obesity (Figure 1, Figure 2, Figure 3), even when Akt is fully sensitive to insulin (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Initial work on adipocyte metabolism in obesity revealed that the biosynthesis of palmitate from acetyl CoA, denoted de novo lipogenesis (DNL), was markedly reduced in the insulin resistant state [19], [20] in spite of near normal glucose uptake [21]. These data suggested a possible role of DNL disruption in insulin resistance of adipocytes that was extended to human adipose tissue [22], [23].…”
Section: Introductionmentioning
confidence: 99%